Determination of enamel insulation corona resistance by high-frequency modulated pulses; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Leonov A. P. Andrey Petrovich; Redko V. V. Vitaliy Vladimirovich; Redko L. A. Lyudmila Anatolevna; Soldatenko E. Yu. Evgeniy Yurievich (2015, 2015)
Title screen